2015
DOI: 10.1111/ffe.12321
|View full text |Cite
|
Sign up to set email alerts
|

Effect of small defect orientation on fatigue limit of carbon steels

Abstract: In order to clarify the effect of defect orientation on the fatigue limit of two types of steels, JIS‐S15C and JIS‐S45C, a small semi‐circular slit was introduced onto the surface of a round specimen. The slit was tilted at 0 °, 30 ° or 60 ° with respect to the plane normal to the loading axis, but all of them had the same defect size, area = 188 µm, where the area denotes the area of the domain defined by projecting the defect on a plane normal to the loading axis. In all the combinations of the materials an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…These results are shown in Fig. 14 [34,[42][43][44] are reasonably consistent within a scatter band described by both models. The scatter band of Fig.…”
Section: Effect Of Induced Surface Defect On Fatigue Strengthsupporting
confidence: 82%
See 2 more Smart Citations
“…These results are shown in Fig. 14 [34,[42][43][44] are reasonably consistent within a scatter band described by both models. The scatter band of Fig.…”
Section: Effect Of Induced Surface Defect On Fatigue Strengthsupporting
confidence: 82%
“…Based on Eqs. (3) and (4), we calculated the values of fatigue limit (fatigue strength at 10 7 cycles) of the present case and several cases in literature [34,[42][43][44], and the calculated values were normalized by experimental data. These results are shown in Fig.…”
Section: Effect Of Induced Surface Defect On Fatigue Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent paper, Lorenzino et al 9 considered the problem of small tilted sharp defects under fatigue loadings. They observed that, for tilted defects, the cracks did not initiate at the notch tip but at a certain distance from the tip, whereas, when the crack was perpendicular to the load direction, the nucleation zone agrees exactly at the notch tip.…”
Section: N O M E N C L a T U R Ementioning
confidence: 99%
“…U-notches of various shapes and under different load directions have been studied over recent years, 21,22 nevertheless the Brazilian disk has become one of the most useful tools for studying this kind of problem in a simple way. First of all, some experimental cases recently presented by Lorenzino et al 9 were analysed according to the implicit gradient (IG) theory. 15,25 The aim of this paper is to analyse when cracks can nucleate in a place near the notch tip in a zone where the stress is not singular.…”
Section: N O M E N C L a T U R Ementioning
confidence: 99%